Perilaku Pencegahan Cacat Pada Pasien Kusta - Srinalesti Mahanani; Iin Nurmasfufah (Jurnal Keperawatan Muhammadiyah, 2020)
Leprosy occurs due to impaired neurological function in the eyes, hands or feet. The principle of the prevention of disability and the severity of disability is essentially 3M: Checking the eyes, hands and feet regularly, protecting the eyes, hands and feet from physical trauma and self-care. The purpose of this study is to study the behavior of prevention of defects and the increase of defects in leprosy patients in the Outpatient Installation of Leprosy Hospital Kediri. The design of this study is descriptive. The population of this research is leprosy patient with purposive sampling technique of 92 subjects. Variables are preventive behaviors, data collection using structured interviews. Analyzed using frequency distribution. The result of this research is 54,3% leprosy patients have defect prevention behavior and less defect and 45,7% of leprosy patients have defect prevention behavior and sufficient defect increase. It was concluded that leprosy patients in the Outpatient Installation of Leprosy Hospital Kediri have defect prevention behavior and less defect increment.